STRATEGI PEMBELAJARAN GERAK MANIPULATIF DALAM MENINGKATKAN KOORDINASI DAN KETANGKASAN PESERTA DIDIK - Lede, Maria Magdalena; Lawe Riwu, Frumensius; Rewo, Josep Marsianus (SMA Negeri 1 Bangkinang Kota, 2026)
This study aims to determine the effect of manipulative movement learning strategies on improving the coordination and dexterity of elementary school students in Physical Education, Sports, and Health (PJOK) learning. This study used a quantitative approach with a quasi-experimental method and a one-group pretest–posttest design. The subjects were elementary school students at SDK Regina Pacis who were selected using a purposive sampling technique. Treatment was given through the implementation of manipulative movement learning strategies based on play activities and simple games adapted to the developmental characteristics of elementary school students. The research instruments included a coordination test in the form of a throwing and catching ball test, an agility test in the form of a shuttle run, and observations during the learning process. Data were analyzed using descriptive statistics and a paired t-test with a significance level of 0.05. The results showed an increase in students' coordination and dexterity after the implementation of the manipulative movement learning strategy. The t-test results showed a significant difference between the pretest and posttest scores (p < 0.05). Furthermore, observations indicate that students are more active, enthusiastic, and confident in participating in Physical Education (PJOK) lessons. Therefore, it can be concluded that manipulative movement learning strategies are effective in improving coordination and dexterity in elementary school students and supporting active and meaningful PJOK learning.